2021
DOI: 10.4049/jimmunol.2001099
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-21 Deficiency Promotes the Early Th1 Immune Response and Resistance toward Visceral Leishmaniasis

Abstract: MicroRNA-21 (miR-21) inhibits IL-12 expression and impairs the Th1 response necessary for control of Leishmania infection. Recent studies have shown that Leishmania infection induces miR-21 expression in dendritic cells and macrophages, and inhibition of miR-21 restores IL-12 expression. Because miR-21 is known to be expressed due to inflammatory stimuli in a wide range of hematopoietic cells, we investigated the role of miR-21 in regulating immune responses during visceral leishmaniasis (VL) caused by Leishma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…These miRNAs presented below in sequence are related to activation or modulation of the immune system and may play a crucial role in Leishmania infection either in the control or progression of the infection. The following miRNAs may contribute to the progression of the infection: a) miR-21 seen up-regulated in dendritic cells, macrophages, inflammatory monocytes, polymorphonuclear neutrophils, and in the spleen and liver tissues after L. donovani infection and in splenic leukocytes from L. infantum -naturally infected dogs and related to the inhibition of IL-12 expression and impairment of the Th1 response implied in the control of the infection ( Melo et al., 2019 ; Varikuti et al., 2021 ); b) miR-302a-3p that regulates receptor activator of nuclear factor kappa-B ligand (RANKL) (a member of the tumor necrosis factor TNF superfamily) that regulates T-cell-dependent immune response and apoptosis ( Irwandi et al., 2018 ) and also up-regulated in in vitro L. braziliensis infection ( Souza et al., 2021 ); c) miR-372-3p that inhibits cell proliferation and apoptosis and seen up-regulated in L. braziliensis infection ( Chen et al., 2015 ; Souza et al., 2021 ). Otherwise, distinct miRNAs may act on the control of the infection: a) miR-340-5p that targets the IL-4, major Th2 cytokines secreted by CD4 + T cells, and this miRNA, different from observed with L. infantum , was down-regulated in in vitro L. donovani infection ( Kumar et al., 2020 ); b) miR-302b-3p that inhibits cell proliferation through the AKT pathway by targeting insulin-like growth factor 1 receptor (IGF-1R) ( Guo et al., 2017 ) and was also up-regulated in in vitro L. amazonensis and L. braziliensis infection ( Muxel et al., 2017 ; Souza et al., 2021 ); c) miR-373-3p that is implicated in the regulation of cell proliferation, apoptosis, senescence, migration, and cell invasion and was up-regulated in L. braziliensis infection ( Wei et al., 2015 ; Souza et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…These miRNAs presented below in sequence are related to activation or modulation of the immune system and may play a crucial role in Leishmania infection either in the control or progression of the infection. The following miRNAs may contribute to the progression of the infection: a) miR-21 seen up-regulated in dendritic cells, macrophages, inflammatory monocytes, polymorphonuclear neutrophils, and in the spleen and liver tissues after L. donovani infection and in splenic leukocytes from L. infantum -naturally infected dogs and related to the inhibition of IL-12 expression and impairment of the Th1 response implied in the control of the infection ( Melo et al., 2019 ; Varikuti et al., 2021 ); b) miR-302a-3p that regulates receptor activator of nuclear factor kappa-B ligand (RANKL) (a member of the tumor necrosis factor TNF superfamily) that regulates T-cell-dependent immune response and apoptosis ( Irwandi et al., 2018 ) and also up-regulated in in vitro L. braziliensis infection ( Souza et al., 2021 ); c) miR-372-3p that inhibits cell proliferation and apoptosis and seen up-regulated in L. braziliensis infection ( Chen et al., 2015 ; Souza et al., 2021 ). Otherwise, distinct miRNAs may act on the control of the infection: a) miR-340-5p that targets the IL-4, major Th2 cytokines secreted by CD4 + T cells, and this miRNA, different from observed with L. infantum , was down-regulated in in vitro L. donovani infection ( Kumar et al., 2020 ); b) miR-302b-3p that inhibits cell proliferation through the AKT pathway by targeting insulin-like growth factor 1 receptor (IGF-1R) ( Guo et al., 2017 ) and was also up-regulated in in vitro L. amazonensis and L. braziliensis infection ( Muxel et al., 2017 ; Souza et al., 2021 ); c) miR-373-3p that is implicated in the regulation of cell proliferation, apoptosis, senescence, migration, and cell invasion and was up-regulated in L. braziliensis infection ( Wei et al., 2015 ; Souza et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Focuses on the interaction between parasites and their hosts have pointed out the critical role of host or parasite originated miRNAs in orchestrating the immune responses and pathogenesis of parasites [40][41][42]. Blastocystis sp., is a prevalent protist, which its pathogenicity is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Their imbalance results in pathogenesis of many kinds of diseases. TNF-α and IFN-γ are Th1-assocaited cytokines, [ 45 ] and Lauffer et al [ 41 ] reported that lichen planus and lupus erythematosus, both of which present histopathological feature of interface dermatitis, shared the significant transcriptomics characteristics of type I immune response. They found that T cells infiltrating in skin lesions were dominated by TNF-α and IFN-γ positive cells.…”
Section: Discussionmentioning
confidence: 99%